Agronomic performance of hybrids and parents of grain sorghum in Huastecas. - Williams-Alanís, Héctor (2015)
The objective of the study was to determine the productivity of experimental hybrids of grain sorghum group in the Huastecas region, contrasting with commercial checks and parents. At Estación Cuauhtémoc, Tamaulipas, Mexico, three trials with 49 experimental and commercial hybrids were established during the spring-summer cycles 2005, 2006 y 2007 in dry land conditions. In 2008 in dry land, a trail was established with 28 hybrids and parents. In all cases we used a randomized block design with four replications. Experimental hybrids were identified as agronomically similar to commercials. One of the best hybrids was RB-104xRTx437, which produced 6403 kg/ha of grain. It was equal (p≤0.05) to: RB-Patron (6288 kg/ha), A. Amber (6028 kg/ha), DK-65 (5763 kg/ha) and RB-4000 (5700 kg/ha) was superior to Pioneer 82G63 (4796 kg/ha), Pioneer 84G62 (4256 kg/ha) and Z-400 (4218 kg/ha). The hybrid was also (p≤0.05) the earliest to flower (62 d) compared to to A. Ambar (65 d) and DK-65 (66 d). The experimental hybrids were higher yielding (2924 kg/ha), taller (17 cm), more precocious (-4.5 DF), had longer panicle length (0.9 cm) and exsercion (3,5 cm), and lower foliar diseases incidence (-0.24) than their parents. RTx437 was the best parent with grain yield (3598 kg/ha) equal (p≤0.05) to the hybrids.